POTENSI MAMALIA BESAR SEBAGAI MANGSA KOMODO (Varanus komodoensis Ouwens 1912) DI PULAU RINCA TAMAN NASIONAL KOMODO NUSA TENGGARA TIMUR - Mustari, Abdul Haris; Djuanda, Tyas D.; Sihite, Jamartin (Media Konservasi, 2016)
This study aimed to reveal the potential of big mammals as komodo’s preys in Rinca Island, Komodo National Park. Population density, sex ratio, age structure and distribution of the komodo’s preys were collected using line transect method, and the vegetation were analyzed using line square method. A total of five species of big mammals were recorded as preys of komodo on the island, and among them were Timor deer and water buffalo which were the most important food sources for komodo. Long tailed macaque, wild horse, and wild boar were the alternative food sources for komodo. Komodo ate whenever there was the opportunity, and it usually attack animals in the savanna or water sources, since these areas were important for big mammals. Keywords: komodo, preys, mammals, population, savanna